2015
DOI: 10.1016/j.buildenv.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Potential airborne transmission between two isolation cubicles through a shared anteroom

Abstract: a b s t r a c tFull-scale experiments and CFD simulations were performed to study potential inter-cubicle airborne transmissions through a shared anteroom due to the hinged door opening. When doors are closed, current negative pressure designs are effective for the containment of airborne pathogens in the 'dirty' cubicle with an index patient. When the 'dirty' cubicle door is open, airborne agents can move into the other 'clean' cubicle via the shared anteroom. As the door being opened or closed, the door swee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 44 publications
0
46
0
1
Order By: Relevance
“…significant downwash that occurs behind the body has the effect of laterally spreading the lower portions of the wake. 59,60 Using large eddy simulation, Choi and Edwards 55,61 found that backward transport (opposite to the direction of walking) can also occur because of downwash effects and tip vortex formation. Wakeinduced transport of material in the direction of the walking motion continues because of inertial effects, even after the person stops.…”
Section: Spread Of Droplets In the Indoor Environmentmentioning
confidence: 99%
“…significant downwash that occurs behind the body has the effect of laterally spreading the lower portions of the wake. 59,60 Using large eddy simulation, Choi and Edwards 55,61 found that backward transport (opposite to the direction of walking) can also occur because of downwash effects and tip vortex formation. Wakeinduced transport of material in the direction of the walking motion continues because of inertial effects, even after the person stops.…”
Section: Spread Of Droplets In the Indoor Environmentmentioning
confidence: 99%
“…In principle, increasing ventilation rates can generate more turbulence which in turn can enhance the mixing across the open doorway [41]. However, it should be noted that in general, increased ventilation rates improve the containment as the concentration of particles and gaseous agents are more quickly diluted already in an isolation room [21,38]. Hence, less agents are dispersed from an isolation room into an anteroom and subsequently less of a fraction can enter other neighboring spaces [21].…”
Section: The Effect Of Ventilation Ratesmentioning
confidence: 99%
“…These heat loads can heat up the rooms and generate temperature difference between an isolation room and an anteroom or a corridor. Already a small temperature difference induces continuous two-way air exchange across open doorway substantially increasing the total air volume migration during door operation [21,53]. This effect becomes increasingly important when door is kept open long periods [20e22].…”
Section: Limitations Of Using a Manikin Set Door Open-close Cycle Timentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the human health concerns necessitate strict observation and control over infection transmission within hospitals for infectious diseases, such as measles, chickenpox, Severe Acute Respiratory Syndrome (SARS), tuberculosis (TB), and in uenza [1]. To implement appropriate infection control measures and prevent the transmission of contagious diseases from a patient to other people or from outsiders, such as health care personnel and visitors, to the susceptible patient, hospitals must have Airborne Infection Isolation Room (AIIR) which is a safe and healthy environment for patients with infectious diseases [2].…”
Section: Introductionmentioning
confidence: 99%